Comparison of the oral microbiota of patients with atherosclerosis and healthy controls by denaturing gradient gel electrophoresis: Oral microbiota and atherosclerosis - Nazari, Zahra; Ramin Abiri; Mohajerani, Hamid Reza (Cellular and Molecular Biology, 2024)
Oral infections can activate local and systemic inflammation. The inflammatory response plays a main role in atherosclerosis. several studies have reported a relation between oral pathogen infection and Atherosclerosis. Recently it was indicated that some oral microbiome has a significant role in triggering atherosclerosis. Denaturing Gradient Gel Electrophoresis (DGGE) is an acceptable assay for identification of uncultivable bacteria. Therefore, we compared the bacterial population diversity in the oral microbiota between atherosclerosis patients and healthy people. Oral microbiota profiling was performed for 139 individuals including 89 patients with CAD and 50 healthy individuals. After DNA extracted from saliva, PCR products were examined and evaluated using DGGE assay. We found that significant relationship between the increased risk of atherosclerosis and the presence of Actinomyces oris, Enterococcus faecalis, Bacterium strain sulresv, Bacterium Culaenoe, NC4, NC7, and NC5 in atherosclerosis patients and healthy individuals. There was also a significant relationship between reducing the risk of atherosclerosis in the presence of NC3 and Entreococcus munotii in atherosclerosis patients and healthy individuals. In conclusion, presence of some oral microbiota increases the risk of atherosclerosis and the presence of some oral microbiota reduces the risk, so the oral microbiota should be further examined to determine its potential as a biomarker for atherosclerosis.